Amor, isto não é um livro, sou eu : um estudo sobre a intimidade na poética de Ana Cristina Cesar - Natália Pereira Buzatti (2023)
This present work starts from the perspective that writing develops an important process of subjectivation, affecting the complex relationship between literature and life. In this context, the sphere of intimacy, since its rise in bourgeois society, occupies a significant place in social life and, in contemporary times, the ways of being in the world, as well as literary expressions, settle into the becoming of the publicity of the intimate. Based on this assumption, we investigated the role that intimacy plays in Ana Cristina Cesar's poetics, undertaking an analysis divided into two parts: (1) firstly, we comparatively analyzed three of the poet's posthumous publications, Inéditos e dispersos (1985), Antigos e Soltos (2008) and Inconfissões (2016), following the hypothesis that these works spectacularize Ana Cristina Cesar's intimacy, her private moments and the intimate issues surrounding her suicide. For this purpose, we associated the instance of death with studies on silence and examined the martyrology character presented by these books. We also investigated the use of the poet's photographs and primary sources to compose this spectacle of intimacy. (2) Secondly, we studied the book Poética (2013), by the same author, selecting her poems in order to analyze how she mischaracterizes the role of intimacy as an element that sustains the correspondence between literature and life. To this end, we investigated the outlines that constitute literary space and how aesthetic resources are boosted in Ana Cristina Cesar's poetry to subvert the relationship between life and literature. Therefore, this dissertation is introduced with a historical-philosophical contextualization of the process of subjectivation through writing and the development of private and public spaces in relation to the intimate sphere and writing, as well as their implications today; it then focuses on the spectacularization of intimacy in Ana Cristina Cesar's posthumous works and their specificities; and concludes by investigating the associations and dissociations that the poet articulates in her prosaic poetry, in relation to the intimate sphere.